Editors’ Preface (Narzędzia wojny, 2023)
The preface concerns the collective monograph devoted to the history of Poland and Ukraine. It contains 12 articles written by Polish and Ukrainian historians. Chronologically, it contains texts from the Middle Ages to the present day.